Intercropping: Farming for the future? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Intercropping: Farming for the future? Until recently, intercropping has received relatively little attention from agricultural scientists, even though it has been practised for centuries by millions of farmers in the tropics and is a system which...